The Influence of Microsite-Based Learning Media on Student Learning Independence in Islamic Education Subjects - Saepudin, Ahmad; Helnanelis, Helnanelis; Mubarok, Asep Syahrul (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
This study aims to examine the effect of using microsite-based learning media on student learning independence in Islamic Religious Education (PAI) subjects at SMAN Cahaya Madani Banten Boarding School. This research employed a quantitative method with a quasi-experimental pretest-posttest control-group design. The subjects were two 11th-grade classes, with one class serving as the experimental group using the microsite media and the other as the control group. Learning independence data were collected through pretest-posttest questionnaires and analyzed using an Independent Sample T-Test. The results showed a significance value (p-value) of 0.024 (p < 0.05), indicating a significant difference in learning independence between the experimental and control groups. Therefore, it can be concluded that the use of microsite-based learning media significantly influences student learning independence.